Aḥmad Nu‘mān, Beyrouth 1969 : l’improbable Yémen - Juliette Honvault (Arabian Humanities)
In 1969, at the age of sixty, Aḥmad Muḥammad Nu‛mān, a leading politician in the history of the republican revolution in Yemen, is in exile in Beirut, after more than a year in an Egyptian jail. There, before a professor of the American University particularly attached to the idea of ​​Arabism, he delivers an account of his transnational struggle for political, social and cultural reform in his country. This article examines the paradigm of contact and transnational exchange as a vehicle for new visions of the world. But what about the interview that gave rise to the narrative? It is clear that, although Nu‛mān explains his transnational activities through a strong feeling of Arabism, his criticism of the policy of Gamal Abdel Nasser in Yemen dominates the narrative: he fails to present Yemen as part of a diverse, creative and vibrant Arab nation.